Economic catch-up and technological leapfrogging the path to development and macroeconomic stability in Korea - Lee, Keun, 1960-; Edward Elgar Publishing (Northampton, MA : Edward Elgar Pub., 2016)
This book elaborates upon the dynamic changes to Korean firms and the economy from the perspective of catch-up theory. The central premise of the book is that a latecomer's sustained catch-up is not possible by simply following the path of the forerunners but by creating a new path or 'leapfrogging'. In this sense, the idea of catch-up distinguishes itself from traditional views that focus on the role of the market or the state in development. The author provides a comprehensive account of the micro and macro level changes, deals with both firm- and country-level capabilities, and explores the issue of macroeconomic stability to overcome financial crisis. The book demonstrates that at the firm level the focus is on innovation capabilities, diversification, internationalization and job creation. It goes on to examine the rise and upgrading of big businesses, such as Samsung, as well as the global success of SMEs. Comprehensive and illuminating, this is an ideal book for students, academics and researchers interested in the economics of development and technological innovation. It will also be a valuable source book for policy makers in international development agencies, governments and the public sector.
1. Introduction -- Part I catch-up and leapfrogging at the economy level -- 2. Historical origins and initial conditions for economic catch-up (with H.Y. Lee) -- 3. Korean model of catch-up development: a 'capability-based view' -- 4. Intellectual property rights and technological catch up -- 5. From miracle to crisis and the mirage of the post-crisis reform (with Chung Lee) -- 6. Maintaining macro stability for a crisis-resilient growth in Korea (with H. Kim, H.S. Song and J. Kim) -- 7. Is leapfrogging-style reform possible in North Korea (with B.Y. Kim and I.S. Yee)-- Part II catch-up and leapfrogging at the sector level -- 8. Catch-up and leapfrogging in the 6 sectors in the 1980s and 1990s (with C. Lim) -- 9. Digital technology as a window of opportunity for leapfrogging: display industry (with C. Lim and W. Song) -- 10. Technological catch-up in capital goods sector (with Y. Kim) -- Part III catch-up and internationalization by big businesses and the SMEs -- 11. Samsung, created in Korea and replicated overseas (with X. He) -- 12. Moving factories overseas and impacts on domestic jobs: case of Samsung (with M. Jung) -- 13. Catch-up and path-creating by SMEs: from OEM to OBM (with J. Kwak and J.Y. Song) -- 14. Sequential internationalization of the Korean SMEs in China (with H. Lee and J. Kwak).
Includes bibliographical references and index.
Description based on print record.
Keywords: Korea (South) -- Economic conditions; Small business; Electronic books